The feeling of life in Kant: teleology, nature, and freedom - Rocha, Leandro José (Con-Textos Kantianos. International Journal of Philosophy, 2025)
This article examines Kant’s concept of the "feeling of life," addressing it as a feeling that transcends mere physiological response and intertwines with the aesthetic, ethical, and teleological domains in Kant’s work. Beginning with an analysis of the organism as a structure endowed with a formative force that coordinates its parts, the feeling of life is explored on three levels: the animal, the human, and the spiritual. Each of these modes reveals distinct facets of the experience of existence, ranging from sensory delight, through the aesthetic appreciation of the beautiful and the sublime, to the moral pleasure of autonomous action. In addition to contributing to the understanding of organisms as teleological entities, the investigation into the feeling of life paves the way for an interpretation of human subjectivity that considers the interdependence between pleasure, freedom, and nature.